The GMO Dispute before the WTO: Legal Implications for the Trade and Environment Debate - Francesco Sindico (Fondazione Eni Enrico Mattei (FEEM), 2005)
USA, Canada and Argentina have challenged before the World Trade Organisation the European Communities (EC) denial of Genetically Modified (GM) product imports, which took place from 1998 to 2004 . Against this background, the goal of this paper is twofold. Firstly, we will determine which WTO provisions would have been violated by the EC. Secondly, we will highlight the disputes most important legal issues in order to see to what extent the dispute might influence the ongoing trade and environment debate. The paper concludes that the role of the precautionary principle in the application of the EC legislation is one of the disputes main issues. Furthermore, the Panel findings on the legal nature of the precautionary principle, and on its relevance for the interpretation of WTO provisions, will finally determine the influence of the GMO dispute on the trade and environment debate.
Keywords: Q00; F10; 330; GMO; WTO; Trade; Environment